PTH-131 Endoscopic Gastropexy And Peg Feeding Tube Insertion: A Comparative Study. (9th June 2014) - Salunke, SS; McKay, R; Barber, D; McKinlay, AW; Leeds, JS
Abstract : Introduction: PEG feeding in patients with head and neck and upper GI cancers is known to derive nutritional and mortality benefits. Standard inside-out PEG insertion is not always technically possible or safe especially when there is narrowing of the oesophagus or pharynx from cancer. There is also concern about tumour seeding with inside-out technique. Similarly, in some patients it is not possible to pass the standard gastroscope through to upper GI tract. Gastropexy is an alternative technique which allows insertion of a gastrostomy tube with outside-in technique and can be performed using ultrathin scopes rather than standard gastroscopes. Gastropexy has been routinely performed in our unit for some time. We aimed to review the experience of Gastropexy insertion in our unit and compare it to age and indication matched controls who underwent PEG insertions. Methods: A retrospective review of institutionally approved PEG database was conducted. Gastropexy insertions between June 2009 and November 2012 and PEG insertions between March 2006 and January 2012 were reviewed retrospectively. Indication and age matched PEGs were used as controls. Patients with cancers (head and neck, oesophageal and other) undergoing the procedure were selected. Patient characteristics, sedation requirement, technical success, success using ultrathin scopes, safety, complications if any and mortality rates were recorded. Results: Fifty four patients received 57 gastropexies (30 males, median age 63 (range 39–84) years); 108 patients received 109 PEG's (55 males, median age 68 (range 20–93) years). Eighty three percent of gastropexy and 97% of PEG's were done under conscious sedation. The remaining gastropexy insertions were done under GA as a part of another surgical procedure. Technical success was achieved in 98 and 100% for gastropexy and PEG's respectively. Minor gastric fluid leak in 1 patient in gastropexy group and mouth bleed in 1 patient in PEG group was noted. No procedure related deaths were noted in either of the groups. Conclusion: In the context of risk from tumour seeding and mucosal trauma to narrowed upper GI tract, endoscopic gastropexy procedure seems non-inferior to PEG's. It seems safe and can be done with high technical success rate. Perhaps, it may be an alternative to PEG in patients with inherently difficult upper GI tract and major illness like cancers. Disclosure of Interest: None Declared.